Management Information System and E-Khairat for Masjid Al-Ikhwan Kampung Kemuning - Megat Anuar, Megat Akmal Syafiq; Kamaludin, Hazalila (Applied Information Technology And Computer Science, 2024)
Masjid Al-Ikhwan currently does not have any web-based system and still using the traditional way for information management. The people of kampung Kemuning still sending invitation using paper, watch religious video from Whatsapp, transfer information of lecture by person and pay funeral expenses manually. Therefore, a web-based Management Information System And E-Khairat for Masjid Al-Ikhwan Kampung Kemuning is developed to ease the people from Kampung Kemuning in getting information, send invitation, pay funeral expenses, and watch religious videos. The main language that being used in the system are HTML, CSS, JavaScript and PHP. While for the database, it uses MySQL to store data. The system should be able to reduce the usage of paper in order to send invitation and reduce the misleading religious video.